Wrocławska Diagnoza Społeczna 2017. Raport z badań socjologicznych nad mieszkańcami miasta - Błaszczyk, Mateusz; Borowik, Iwona; Dolińska, Kamilla; Kłopot, Stanisław W.; Kozdraś, Grzegorz; Krysiński, Dawid; Makaro, Julita; Żurek, Grzegorz (Uniwersytet Wrocławski)
Social Diagnosis of Wroclaw 2017 is the third consecutive, complex social research on the inhabitants of the city of Wroclaw. Earlier editions took place in 2010 and 2014 providing extensive comparative empirical material. In this edition particular attention was given to the themes of: quality of life in households, quality of life in urban settlements, quality of public services, urban system of consumption, neighbourhood relations, leisure time infrastructure, labour market, urban policies and attitudes towards migrants. Social Diagnosis of Wroclaw 2017 is a quantitative research on many aspects of urban life. The research process was carried out using CAPI technique (computer assisted personal interview) and Random Route sampling method. In total, 2001 inhabitants of the city, aged 15-80, participated in the research. Variables of gender and age as well as the spatial distribution of interviewees in 29 areas aggregating 49 administrative districts were controlled by the researchers.
Keywords: social diagnosis; quality of life; urban settlements; social problems; leisure; urban amenities; system of consumption